Effects of natural starch-phosphate monoester content on the multi-scale structures of potato starches. (15th June 2023) - Ding, Li; Liang, Wenxin; Qu, Jianzhou; Persson, Staffan; Liu, Xingxun; Herburger, Klaus; Kirkensgaard, Jacob Judas Kain; Khakimov, Bekzod; Enemark-Rasmussen, Kasper; Blennow, Andreas; Zhong, Yuyue
Abstract: Starch phosphate content (SPC) is an important structural parameter affecting the functionality of tuber starches, but how different phosphate groups affect starch structures is still unknown. In this study, four potato starches with different SPC were selected as models to investigate the effects of SPC on their multi-scale structures. A higher SPC is related to more long amylopectin (AP) chains with a degree of polymerization (DP) >24, fewer short AP chains with DP ≤ 24, lower double helical content and crystallinity, higher long period distance, and lower scattering intensity ( I max ), indicating that potato starch with a higher SPC is less ordered and has a more flexible nano-lamellar structure. Notably, two types of phosphate monoesters, namely C-3 (C3P) and C-6 phosphate monoesters (C6P), were both significantly positively correlated with the average chain lengths (ACL) of AP chains with DP 25–36 (fb2) and negatively correlated with I max ; however, only C3P was significantly positively correlated with ACL of AP chains with DP 13–24 (fb1) and negatively correlated with the absorbance ratio at 1047/1016 cm −1 . C3P was the main reason for the disordered structure of starches with high SPC. These findings can be helpful for potato breeding to generate different functionality by controlling SPC. Graphical abstract: Unlabelled Image Highlights: Starch with high starch phosphate content (SPC) had a low structural ordering. C-3 phosphate monoesters (C3P) disordered the lamellar structure. C3P was negatively correlated with the absorbance ratio at 1047/1016 cm −1 . C3P was the main cause for the low structural ordering of starch with high SPC. Amylose content also disordered granular structures in potato and maize systems.